Dynamin Inhibitors Impair Endocytosis and Mitogenic Signaling of PDGF. (12th March 2013) - Sadowski, Łukasz; Jastrzębski, Kamil; Kalaidzidis, Yannis; Heldin, Carl‐Henrik; Hellberg, Carina; Miaczynska, Marta
Abstract : Platelet‐derived growth factor (PDGF) isoforms regulate cell proliferation, migration and differentiation both in embryonic development and adult tissue remodeling. At the cellular level, growth‐factor signaling is often modulated by endocytosis. Despite important functions of PDGF, its endocytosis remains poorly studied, mainly for lack of tools to track internalized ligand by microscopy. Here, we developed such a tool and quantitatively analyzed internalization and endosomal trafficking of PDGF‐BB in human fibroblasts. We further show that PDGF can be internalized in the presence of dynamin inhibitors, arguing that both dynamin‐dependent and dynamin‐independent pathways can mediate PDGF uptake. Although these routes operate with somewhat different kinetics, they both ultimately lead to lysosomal degradation of PDGF. Although acute inhibition of dynamin activity only moderately affects PDGF endocytosis, it specifically decreases downstream signaling of PDGF via signal transducer and activator of transcription 3 (STAT3). This correlates with reduced expression of MYC and impaired cell entry into S‐phase, indicating that dynamin activity is required for PDGF‐induced mitogenesis. Our data support a general view that the components governing endocytic trafficking may selectively regulate certain signaling effectors activated by a growth factor.